On migration and immigration policy in Europe - Charmaine Fritsche (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2021)
To which countries do people migrate? What role does income play in drawing migrants to certain countries? This essay attempts to answer these questions. It also presents a comprehensive overview of migration theories as well as worldwide trends in migration. Shrinking populations in high-income countries indicate that a demand for migrants exists. Empirical data on 155 countries shows that migration to a specific region can be explained as a function of income or per capita gross domestic product (GDP) of this country. It establishes the direction of flow of migrants from low-income to high-income countries. Regulating the demand for and supply of migrants together in the European context requires government intervention in the form of a more comprehensive, legal and unified migration policy.
Keywords: 330